Quality standards in upper gastrointestinal endoscopy: a position statement of the British Society of Gastroenterology (BSG) and Association of Upper Gastrointestinal Surgeons of Great Britain and Ireland (AUGIS). Issue 11 (18th August 2017) - Beg, Sabina; Ragunath, Krish; Wyman, Andrew; Banks, Matthew; Trudgill, Nigel; Pritchard, Mark D; Riley, Stuart; Anderson, John; Griffiths, Helen; Bhandari, Pradeep; Kaye, Phillip; Veitch, Andrew
Abstract : This document represents the first position statement produced by the British Society of Gastroenterology and Association of Upper Gastrointestinal Surgeons of Great Britain and Ireland, setting out the minimum expected standards in diagnostic upper gastrointestinal endoscopy. The need for this statement has arisen from the recognition that while technical competence can be rapidly acquired, in practice the performance of a high-quality examination is variable, with an unacceptably high rate of failure to diagnose cancer at endoscopy. The importance of detecting early neoplasia has taken on greater significance in this era of minimally invasive, organ-preserving endoscopic therapy. In this position statement we describe 38 recommendations to improve diagnostic endoscopy quality. Our goal is to emphasise practices that encourage mucosal inspection and lesion recognition, with the aim of optimising the early diagnosis of upper gastrointestinal disease and improving patient outcomes.